R&D expenditure and the role of scientists - Białek-Jaworska, Anna; Dobroszek, Justyna (Wydatki na B+R i rola naukowców, 2019)
An effective knowledge-based economy requires regular cooperation between science and business. This is possible thanks to enterprises that create and implement innovations The paper focuses on the recognition of R&D expenditure. This aims to verify if firms with a scientist on their board are more likely to invest in the R&D. We conduct a tobit panel analysis of over 18,000 Polish private firms combined with data on patents and scientists employed at universities. The findings show that firms with scientists on the supervisory board are likely to invest more in R&D. However, these investment in R&D of firms with a scientist on the board are financial constraint. Their growth depends on access to finance. Therefore, institutions in Poland should support and promote cooperation between science and business, aiming for the realization of the implementation research. This approach requires updated regulations in the accounting area relating to the recognition of R&D inputs and outcomes
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 2, s. 1-16
Keywords: R&D; dynamic entrepreneurship; academic entrepreneurship; innovation; scientist; family business; B+R; dynamiczna przedsiębiorczość; akademicka przedsiębiorczość; innowacje; naukowiec; firma rodzinna